2021
DOI: 10.4236/tel.2021.113034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Real Exchange Rate on Trade Balance in Cote d’Ivoire: Evidence from Threshold Nonlinear ARDL Model

Abstract: The objective of this paper is to shed new light on the nonlinear relationship between real exchange rate changes and trade balance in Cote d'Ivoire. In examining this issue, previous studies have relied on the nonlinear autoregressive distributed lag model developed by Shin et al. (2014) where real exchange rate is decomposed into partial sum of positive and negative changes. They fail to examine the response of the trade balance to extreme changes in the real exchange rate. In order to investigate possible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…It was thus discovered that, in the long run, the gross domestic product of Turkey and the European Union countries has a positive and large impact on the trade balance, whereas the appreciation of the real exchange rate and oil prices has a significant negative impact on the trade balance. The findings are in line with the findings of other authors (Keho, 2021b). The author studied Ivory Coast's non-linear link between the actual exchange rate movements and the trade balance.…”
Section: Literature Reviewsupporting
confidence: 90%
“…It was thus discovered that, in the long run, the gross domestic product of Turkey and the European Union countries has a positive and large impact on the trade balance, whereas the appreciation of the real exchange rate and oil prices has a significant negative impact on the trade balance. The findings are in line with the findings of other authors (Keho, 2021b). The author studied Ivory Coast's non-linear link between the actual exchange rate movements and the trade balance.…”
Section: Literature Reviewsupporting
confidence: 90%
“…Hashani et al (2022) also claimed that PC and EG showed a positive relationship in Western Balkan countries. Furthermore, Jain (2022) confirmed that demand-led economic growth in BRICS economies, and Keho (2021) revealed that household consumption motivated the high production that positively led to economic growth in Cote d'Ivoire. Koyuncu and Unal (2020) also showed that PC had a positive long-run influence on the EG in Turkey.…”
Section: Private Consumption and Economic Growthmentioning
confidence: 98%
“…One, from a statistical point of view, the logarithmic transformation mitigates fluctuations of individual variables increasing the likelihood of stationarity after first differencing. And two, from an economic point of view, the logarithmic transformation allows the first differences of the variables to be interpreted as growth rates and coefficients in terms of elasticity (Keho, 2021;Waiswa, 2023b).…”
Section: Datamentioning
confidence: 99%